The effect of micronutrients on postpartum pelvic organ prolapse patients - Rahajeng; Mukhamad Nooryanto; Muhammad Dzikrifishofa (Universitas Airlangga, 2023)
HIGHLIGHTS Serum vitamin D levels were significantly different between POP and in healthy women. Micronutrient MMP-1 expression is increased in POP patients. ABSTRACT Objective: Pelvic Organ Prolapse (POP) is when pelvic tissues sink into the vagina due to weakened ligaments or muscles. POP is common globally. Adequate nutrition, including Vitamin D, is vital for prevention. Vitamin D maintains bone and muscle health, regulates MMP-9 to control collagen, essential for pelvic support. Increased MMPs lead to collagen breakdown and POP. Recognizing vitamin D's role in collagen and POP is crucial for prevention. This study aimed to determine definitive association between vitamin D, collagen type I and MMP-1 in POP patients. Materials and Methods: Our search yielded 1375 studies, of which 7 were included in the present investigation. Two studies addressed the micronutrient status of vitamin D, four investigated the micronutrient status of type 1 collagen, and two studied the micronutrient status of MMP-1 in postpartum POP patients. Results: The results showed that the mean of vitamin D levels from POP group was substantially decreased compared to a those of healthy women in the control group (95% confidence interval (CI), -3.64; -3.44 and p <0.05). There was a decrease of collagen I protein in POP (95% CI, -3.26; -2.45. p <0.05). Additionally, MMP-1 expression increased in POP patient (95% CI. 1.48-2.23, p <0.05) Conclusion: Micronutrient status was severely compromised in POP group compared to control subjects.